Vergleich von MRT- und SPECT-Befunden bei Patienten mit zerebraler Mikroangiopathie - Reiche, W.; Weiller, C.; Weigmann, R.; Kaiser, H.-J.; Büll, U.; Schneider, R.; Ringelstein, E. B. (Nuklearmedizin - NuclearMedicine, 1991)
Lacunar infarctions and periventricular hypodensity are assumed to be typical CT patterns of cerebral microangiopathy (MA). In 17 patients with such findings and in 6 controls without any signs of central nervous system disease cranial CT, MRT and 99mTc-HMPAO-SPECT were employed. In 7 patients with CT findings of minor MA demonstrated in comparison to controls no significant difference. In 10 cases with CT findings of pronounced MA periventricular rCBF was significantly reduced compared to controls. rCBF of temporal and parietal cortex were not diminished compared to controls. In 14 patients studied with MRT deep white matter lesions were found which appeared solitary, multiple or confluent. Employing 99mTc-HMPAO-SPECT, cerebral MA revealed rCBF reduction in periventricular brain tissue by cerebellar standardization.